A Comparative Study Between an Oil-in-Water Emulsion and Nonlipid Eye Drops Used for Rewetting Contact Lenses. Issue 6 (November 2015) - Guthrie, Sarah E.; Jones, Lyndon; Blackie, Caroline A.; Korb, Donald R.
Abstract : Objectives: The purpose of this study was to determine the clinical impact of using SYSTANE BALANCE Lubricant Eye Drops (Alcon, Fort Worth, TX), an oil-in-water emulsion, as a rewetting eye drop in symptomatic contact lens wearers. Methods: Subjects who had previously experienced contact lens discomfort (CLD), with a mean lens wearing history of 18.6±12.8 years, were randomly assigned to use a Test (SYSTANE BALANCE Lubricant Eye Drops; n=76) or control (habitual nonlipid contact lens rewetting eye drop; n=30) drop over their contact lenses within 5 min of lens insertion and then subsequently at 2 hr intervals up to a maximum of 4 drops per eye daily for a 1-month period. Assessments of subjective comfort, comfortable wearing time, lid wiper epitheliopathy (LWE), and corneal staining were conducted at baseline and after 1 month, after 6 hr of lens wear. Results: Comfort, wearing time, LWE, and corneal staining all showed statistically significant improvements in the test group using SYSTANE BALANCE Lubricant Eye Drops at the 1-month visit compared with baseline data (all P <0.01) and compared with the control group at the 1-month visit ( P <0.01, P =0.01, P <0.01, and P =0.03, respectively). Conclusions: The use of SYSTANE BALANCE Lubricant Eye Drops as a rewetting drop in a group of wearers who experienced symptoms of CLD improved subjective comfort scores, increased comfortable wearing time, and reduced signs of LWE and corneal staining, when compared with the use of non–lipid-containing contact lens rewetting eye drops.